Negotiating better teamwork. role description and feedback form / Part two, - Collins, William, active 2024, (SAGE Business cases., 2024)
Alex, Bobby, Chris, Dale, Eden, Frankie, and Gale are members of an MBA program team with various personalities and challenges. Each member has their own unique perspective and issues within the team dynamics. They approach Lee, the team leader, seeking his understanding, support, or cooperation to address their individual concerns and conflicts within the team.